Hubungan Lingkungan Tanah Dengan Virulensi Jamur Entomopatogen Pada Tanaman Padi - Rose Novita Sari Handoko; Aminudin Afandhi; Amin Setyo Leksono; Mufidah Afiyanti (Folium : Jurnal Ilmu Pertanian, 2022)
High ecosystem diversity can control pest populations. Rice is a staple food that continues to be researched for interesting things. Indonesia is ranked 3rd for production at the international level. The research was conducted through a survey of plants and paddy fields with conventional application in Kasembon Malang. Standard chemical fertilizer and pesticide application were used in this field. A total of 5 diagonally determined soil sample points were used in this study. The dilution method was carried out for the analysis of entomopathogenic fungi which were then tested using the Koch’s Postulate method on Tenebrio molitor, then observed the symptoms and mortality of Spodoptera litura during the pathogenicity test. The diversity value also demonstrated a medium diversity. We conclude that an application of pesticides and chemical fertilizer according to recommended practices, are not negatively affect the diversity of entomopathogenic fungi. Aspergillus sp and Penicilium sp can cause death against Spodoptera litura.